Cross-cultural barriers and facilitators of dementia care in Arabic-speaking migrants and refugees: Findings from a narrative scoping review - Mohamed Taiebine; Abdelghafour Marfak; Wafaa Al Hassani; Chakib Nejjari (Clinical Epidemiology and Global Health, 2024)
Background/aims: Given the epidemiological disparities and sociocultural shifts in the context of globalization, providing specialized and appropriate care to people living with dementia has become challenging for various ethnic minorities, particularly Arabic migrants and refugees in their host countries. This scoping review aimed to identify cross-cultural barriers and facilitators in dementia care for this population. Methods: A literature review was conducted in July 2023 following Arksey and O'Malley's (2007) framework. The search strategy included articles published in English that addressed dementia care for Arabic migrants, refugees and their caregivers in their host countries. The search engines included PubMed, Scopus, and the Web of Science. Demographic features, clinical manifestations, factors, barriers, and facilitators of dementia care were summarized. Results: Out of 25 studies have been found, 21 full-text articles were assessed for eligibility. Seven articles were included in this review based on inclusion and exclusion criteria. The principal barriers included lack of health communication (translators and interpreters), clear guidelines and strategies to establish cultural dementia care. Facilitators should include capacity building, training of healthcare practitioners, translators/interpreters about dementia assessment and care, sharing of evidence-based practice, and enabling cross-cultural adaptation of best interventions in dementia care. Conclusion: This study aimed to outline the current state of the literature on dementia care for Arabic migrants and refugees. Effective policymaking, cultural awareness, inclusion, and equity are needed in dementia care to respond culturally and linguistically to the unique characteristics of each Arabic migrant or refugee population.